Primer registro para México de Aleurothrixus myrtacei Bondar, 1923 (Hemiptera: Aleyrodidae), sus hospederos y distribución - Sánchez-Flores, Oscar Ángel; Carapia-Ruíz, Vicente Emilio; García-Martínez, Oswaldo; Castillo-Gutiérrez, Antonio (Instituto de Ecología, A.C., 2018)
The first record for Mexico of Aleurothrixus myrtacei Bondar (Hemiptera: Aleyrodidae) is presented and also as host the mistletoe Phoradendron macrophyllum Spreng., on the road Coatzacoalcos-Salina Cruz, El Morrito, Asuncion Ixtaltepec, Oaxaca.